EFEK ASAM METOKSIASETAT (MAA) TERHADAP KUALITAS EMBRIO MENCIT (Mus musculus) SWISS WEBSTER TAHAP PRAIMPLANTASI - Ibrahim, Mustamin (Jurnal Sainstek, 2008)
The effects of methoxyacetic acid on embrio development had been studied. Female mice were mated in the afternoon and the presence of vaginal plug next morning was determined as day 0 of pregnany. On the day 1 of pregnancy, female mice of treated groups were adminintered with a dose of MAA 2 mmol/kg b.w. by gavage, whereas the control groups were administered with serilized ditilled water with the same volume. On the day 3 of pregnancy, pregnan mice from treated groups and control groups were sacrificed by cervical dislocation and dissected. Observations were done on the number of 8 cell embryos, uncompacted morule, compacted morulae, early bastocyst, late blastocyst and abnormal embryos. Observation of number of blastomers was done in day 3.5 of pregnancy using Tarkowskysḿethod. The results showed that single dose of MAA 2 mmol/kg b.w. decreased the percentage of embryos that reached late blastocyst significantly (P